Analysis of Students Learning Difficulties in Advanced Differential Equation Courses Reviewed from the Use of Learning Media During the Covid-19 Pandemic - Inayah Rizki Khaesarani (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2021)
The inability of students to master the material concept of the advanced differential equation gives rise to internal and external factors that are formed in them so that it needs to require encouragement as effective use of learning media so that learning in the classroom becomes increasingly attractive to students. We used online learning media as zoom, offline or online learning videos, E-learning, and others. This research aimed to identify and describe students learning difficulties in advanced differential equation courses in terms of the use of learning media during the Covid-19 pandemic. The type of research used is qualitative research, with a descriptive approach. Results showed that students have great difficulty learning numerical methods to solve first-order differential equations from all three sub-chapters of matter. In this material, students are still less careful in answering questions (58,1%). Because students could not identify the type of methods used to solve problems, students need online learning media that are effective for math learning, such as offline learning videos (71%), as a solution to save internet quotas. So, this research is useful for educators/lecturers in observing the condition of student learning difficulties given the use of learning media used to motivate students to be active in learning advanced differential equation courses during the Covid-19 pandemic.